Treeline monitoring in the San Juan Basin tundra: a pilot project, 2012 - Kummel, Miroslav, author; Rodda, Gordon, author; Fink, Michelle, author; Rondeau, Renée Jane, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2012)
In order to monitor the effects of climate change in the San Juan alpine, the Colorado Natural Heritage Program (CNHP) set up permanent monitoring plots near treeline, the most likely area to notice tree and shrub recruitment. We field checked three sites (Lizard Head Pass, Kendall Mountain, and Deer Creek Park) prior to choosing the Deer Creek Park area near Kendall Mountain and Silverton. In addition to the field work, we conducted a GIS analysis to detect changes in treeline and tree density between the years 1951 and 2011. This report discusses the methods and results of the field monitoring and GIS analysis and describes a scenario to expand this project to more sites within the San Juan Mountains.
Keywords: subalpine zone; alpine zone; alpine tundra; growing season; mountain ecosystem; San Juan alpine; GIS analysis; detailed mapping